1994
DOI: 10.1002/jnr.490380612
|View full text |Cite
|
Sign up to set email alerts
|

Human neurocytoma cells in culture show characteristics of astroglial differentiation

Abstract: Cultured human neurocytoma cells from two neurosurgical patients were analysed for their immunocytochemical staining patterns and growth characteristics. In both cases, the cells stained positive for glial acidic fibrillary protein (GFAP) within one day of tissue culture in medium, with and without fetal calf serum, whereas the histological tumor specimens were negative. Both cases contained cells concomitantly expressing GFAP and synaptophysin (SNP) in the primary cultures. Epidermal growth factor (EGF) was m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
15
1

Year Published

1998
1998
2016
2016

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 44 publications
(18 citation statements)
references
References 33 publications
2
15
1
Order By: Relevance
“…On the contrary, cAMP increases glial differentiation in primary cultures of cells isolated from developing rat cortex (McManus et al, 1999;Grimaldi, 1999). Although astroglial differentiation of neurocytoma cells has been previously reported after longterm culture (Westphal et al, 1994;Ishiuchi et al, 1998;Westphal et al, 1998), the effect of forskolin was first demonstrated in neurocytoma cells in this study.…”
Section: Discussioncontrasting
confidence: 39%
See 1 more Smart Citation
“…On the contrary, cAMP increases glial differentiation in primary cultures of cells isolated from developing rat cortex (McManus et al, 1999;Grimaldi, 1999). Although astroglial differentiation of neurocytoma cells has been previously reported after longterm culture (Westphal et al, 1994;Ishiuchi et al, 1998;Westphal et al, 1998), the effect of forskolin was first demonstrated in neurocytoma cells in this study.…”
Section: Discussioncontrasting
confidence: 39%
“…Interestingly, glial fibrillary acidic protein (GFAP) has been also found in neurocytomas (Von Deimling et al, 1990Deimling et al, , 1991Ishiuchi and Tamura, 1997). The GFAP expression was originally believed to be due to reactive astrocytes located in freshly isolated neurocytomas (Kubota et al, 1991;Figarella-Branger et al, 1992) as well as in cultured neurocytoma cells (Westphal et al, 1994;Westphal et al, 1998). Thus, it remains to be determined whether the cells in neurocytomas have a potential to differentiate into both neurons and astrocytes, or neurocytomas are mixtures of neurons and glial cells.…”
Section: Introductionmentioning
confidence: 99%
“…The name 'ganglioglioneurocytoma' has been proposed for these tumors [7,14,16]. It has been suggested that neurocytomas may arise from progenitor cells that have the capability of differentiating along both neuronal and glial lineages [20].…”
Section: Discussionmentioning
confidence: 99%
“…However, to date neurobiological characterization of neurocytomas remains obscure. Astroglial differentiation was previously reported (Westphal et al, 1994); however, long-term cultures of neurocytomas and neuronal production in vitro have not been accomplished, and precise characterization of differentiational behavior of neurocytoma cells remain to be elucidated. Recently, we have utilized an in vitro system to facilitate and clarify these issues of human central neurocytoma in three patients, and we present that study and the results herein.…”
Section: Introductionmentioning
confidence: 98%